2011
DOI: 10.1007/s11259-011-9472-z
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor mRNA expression, iNOS gene polymorphism and serum nitric oxide levels in indigenous chickens

Abstract: Toll-like receptor (TLR) family is one of the important members of innate immune system that recognizes conserved microbial patterns and induces innate immune response. They also act as a link to adaptive immune response. Nitric oxide (NO) is a multi-functional mediator with diverse physiological and immunological roles. In the present study TLR mRNA expression in heterophils, serum nitric oxide level and iNOS (inducible Nitric Oxide Synthase) gene polymorphism were investigated in cockerels of two Indian nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
2
5
0
1
Order By: Relevance
“…NRAMP-1 and iNOS gene fragments were amplified at an annealing temperature of 60 o C for 20 seconds using the ESCO Thermocycler machine. This result is in accordance with the result reported by Muhsinin et al (2016), but different from the result reported by Liu et al (2016) and Ramasamy et al (2011) at annealing temperature that has been carried out for the primers of NRAMP-1 exon 11 and iNOS intron 24 gene fragments, each at 64 o C for 90 seconds and 55 o C for 1 minute.…”
Section: Discussionsupporting
confidence: 84%
“…NRAMP-1 and iNOS gene fragments were amplified at an annealing temperature of 60 o C for 20 seconds using the ESCO Thermocycler machine. This result is in accordance with the result reported by Muhsinin et al (2016), but different from the result reported by Liu et al (2016) and Ramasamy et al (2011) at annealing temperature that has been carried out for the primers of NRAMP-1 exon 11 and iNOS intron 24 gene fragments, each at 64 o C for 90 seconds and 55 o C for 1 minute.…”
Section: Discussionsupporting
confidence: 84%
“…Second, the mutation could change the regulatory function of that intronic region. Ramasamy et al (2011) did not find any association between different genotypes of iNOS and the level of nitric oxide in Indian native breeds. However, sampling in that study was performed at 44 weeks of age without bacterial challenge.…”
Section: Cd44mentioning
confidence: 57%
“…The first, the Cobb400, is a commercial broiler line used widely in India that is descended from Cobb500 and Cobb100 hybrids, the latter of which had previously been acclimatized within India ( 23 ). The second was the indigenous Indian Kadaknath chicken, a breed prized for its “black” meat, reported to be resistant to some infectious diseases ( 24 , 25 ), and to present immune parameters distinct from those of modern commercial broiler chickens ( 26 , 27 ).…”
Section: Methodsmentioning
confidence: 99%